Challenges of Industry Revolution 4.0 Towards Human Resource Practices Among Manufacturing Companies in Johor - Wan Yusoff, Wan Fauziah (Research in Management of Technology and Business, 2023)
To survive in global business the manufacturing industry needs a high level of skills of the employees to qualify employees to shift their capacities to workspaces with more complex processes and ensure the retention of jobs in changing working environments especially to coop with the implementation of industry Revolution 4.0 (IR 4.0). As the IR 4.0 very much affect the human resource practices, it needs to be well planned and managed. Nevertheless, this issue was not yet fully explored in Malaysia. Thus, the aim of this study is to explore the challenges of Industry Revolution 4.0 towards HR Practices among manufacturing companies in Johor. To achieve this study objective, this study employed qualitative interviews involving 15 Human Resource Managers of manufacturing companies in Johor. The data analysis has been analysis using thematic analysis. This study discovered that four main challenges that manufacturing companies will face and need to be addressed before adopting IR 4.0 include necessary skills, future employment issues, human labor dilemma and superficial conflict. Hence, despite the benefits of IR 4.0 the adoption of IR 4.0 among manufacturing companies in Malaysia need further analyses.